2014
DOI: 10.1002/jat.2975
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of colloidal nanosilver in zebrafish embryos

Abstract: A variety of consumer products containing silver nanoparticles (Ag NPs) are currently marketed. However, their safety for humans and for the environment has not yet been established and no standard method to assess their toxicity is currently available. The objective of this work was to develop an effective method to test Ag NP toxicity and to evaluate the effects of ion release and Ag NP size on a vertebrate model. To this aim, the zebrafish animal model was exposed to a solution of commercial nanosilver. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
(97 reference statements)
0
22
0
Order By: Relevance
“…The ICP-MS data showed that exposure to S4 AgNPs from 4 to 96 hpf resulted in significantly enhanced silver uptake in zebrafish larvae, while no significant differences were observed in the silver uptake levels upon exposure to S10 AgNPs. Previous studies have shown that the size (and coating/suspension media) of AgNPs can determine the level of uptake [11,26,27], suggesting that the smaller size ranges up to 20 nm are more likely to be taken up than larger sized AgNPs. Bar-Ilan et al [26] also reported that the biological impacts observed, including various morphological malformations and yolk sac oedema, significantly increased following exposure to 3 nm range AgNPs from 4-120 hpf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICP-MS data showed that exposure to S4 AgNPs from 4 to 96 hpf resulted in significantly enhanced silver uptake in zebrafish larvae, while no significant differences were observed in the silver uptake levels upon exposure to S10 AgNPs. Previous studies have shown that the size (and coating/suspension media) of AgNPs can determine the level of uptake [11,26,27], suggesting that the smaller size ranges up to 20 nm are more likely to be taken up than larger sized AgNPs. Bar-Ilan et al [26] also reported that the biological impacts observed, including various morphological malformations and yolk sac oedema, significantly increased following exposure to 3 nm range AgNPs from 4-120 hpf.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of molecular response, several studies have previously analysed various gene expressions in fish species in response to AgNP exposure, reporting significant changes in oxidative or general stress [13,14,16,27], toxicological [36,37] and morphological/neural development end-point markers [16,22]. HIF4 mRNA expression was significantly elevated in S4-AgNP-treated embryos, which was indicative of a hypoxic cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly different between the treated and control groups (*P < 0.05; **P < 0.01); and between the 24-and 48-h groups ( composed of more innocuous materials, such as titanium . It is argued whether the toxic effects of Ag NPs are as a result of the size of NPs, the release of ions or both factors (Zhao and Wang, 2011;Beer et al, 2012;Olasagasti et al, 2014). There is currently no standard toxicity test available in the field of nanotoxicology.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several decades, people not only care more about the toxicity and transportation of nanomaterials in the environment, but also have begun to focus on the probable health harms to living organisms [ 3 , 4 , 5 ]. The toxicity of nanoparticles (TiO 2 , ZnO, Ag, Cu, Al, carbon nanotubes, and so on) to living species has been studied in a wide range, including algae, higher plants, animals, and even humans [ 6 , 7 , 8 , 9 , 10 ]. For example, Atha et al proposed that copper oxide nanoparticles strongly inhibited grassland plant growth and induced DNA damage as well as cyanobacteria, which are ancient prokaryotic microorganisms, by generating excess formation of reactive oxygen substances (ROS) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%